Shifting memories : the Nazi past in the new Germany - Neumann, Klaus 1958- (Social history, popular culture, and politics in Germany, 2000)
Salzgitter : a city coming of age -- A Hasenjagd in Celle -- Postwar reconstruction in Hildesheim -- Survivors -- Antifascism and anti-anti-Semitism -- Remembering twenty victims and one perpetrator -- The contested life of Wilhelm Hammann -- Weimar and "the great intellectual designs of the past" -- The lakes and locks of Fürstenberg -- The search for a comprehensive memorialization -- Streets of memory